The Gender-Sensitive University A Contradiction in Terms? - Drew, Eileen; Canavan, Siobhán (Taylor & Francis, 2020)
The Gender-Sensitive University explores the prevailing forces that pose obstacles to driving a gender-sensitive university, which include the emergence of far-right movements that seek to subvert advances towards gender equality and managerialism that promotes creeping corporatism. This book demonstrates that awareness of gender equality and gender sensitivity are essential for pulling contemporary academia back from the brink. New forms of leadership are fundamental to reforming our institutions. The concept of a gender-sensitive university requires re-envisioning academia to meet these challenges, as does a different engagement of men and a shift towards fluidity in how gender is formulated and performed. Academia can only be truly gender-sensitive if, learning from the past, it can avoid repeating the same mistakes and addressing existing and new biases. The book chapters analyse these challenges and advocate the possibilities to 'fix it forward' in all areas. Representing ten EU countries and multiple disciplines, contributors to this volume highlight the evidence of persistent gender inequalities in academia, while advocating a blueprint for addressing them. The book will be of interest to a global readership of students, academics, researchers, practitioners, academic and political leaders and policy makers who share an interest in what it takes to establish gender-sensitive universities.